PEMIKIRAN EKONOMI ILMUWAN MUSLIM INDONESIA (A.M. SYAIFUDDIN, M. DAWAM RAHARJO, KUNTOWIJOYO) - Nur Nabila; Rizkafaiza; Muhammmad Hadziq Ulil Abshor; Ardiyansah Ilham; Muhammad Taufiq Abadi; Muhammad Aris Syafi’i (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This research aims to explain the economic thought of Indonesian Muslim scientists (AM. Syaifuddin, Muhammad Dawam Raharjo, Kuntowijoyo). This research uses literature review from journals and websites.In general, it can be concluded that AM. Syaifuddin, Muhammad Dawam Raharjo, and Kuntowijoyo are three figures who contributed greatly to the development of Islamic economic thought. They discuss various aspects of economics, such as sharia, wealth distribution, and social obligations in Islamic economics. Overall, the Islamic economic thought of these three figures provides a solid foundation for building an economic system that is just, sustainable and based on Islamic moral values. By understanding their roles, people can build a more inclusive and equitable economy that is in accordance with Islamic economic principles.